(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The works of Mahmud Zamakhshari are widely distributed throughout the world funds, libraries and museums. It has been impossible for centuries to fully embrace Zamakhshari’s legacy. For this reason, the approaches to the heritage of the scientist learned by many Zamakhshari scholars who worked in different regions and at different times also differed. The article analyzes editions, manuscripts and information about only named works by Mahmud Zamakhshari.